Re-orientating the mind’s body: perception without vision in a visual world - Makhlouf, Alexandra (My University, 2022)
This auto-ethnography serves to document a particular moment – that of finding myself having to navigate the social and material world after becoming blind; in essence, it is a record of how I had to ‘re-orientate the mind’s body’. In making sense of my new positionality, I was aided by thinkers from many fields, ranging from affect theory, to Crip theory, to cognitive neuroscience. While learning to navigate everyday life, it was also necessary to understand if and how I could continue in my artistic practice, a visual practice without vision.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Arts to the Faculty of Humanities, School of Arts, University of the Witwatersrand, Johannesburg, 2022
Keywords: Auto-ethnography; Artist; Vision